Can communities of policy practice spur food systems innovation? - Pye-Smith, Charlie; Maru, Joyce (CGIAR System Organization, 2023)
We need to make our food systems more productive and resilient if we are to meet growing demand and cope with environmental shocks such as extreme weather events. However, agrifood policies are often poorly coordinated. To tackle this problem, One CGIAR has established an initiative on National Policies and Strategies (NPS). A key component involves supporting Communities of Policy Practice (CoPPs).